2019
DOI: 10.15517/pensarmov.v17i1.35494
|View full text |Cite
|
Sign up to set email alerts
|

Entrenamiento De Intervalos De Alta Intensidad (Hiit) en Adultos Mayores: Una Revisión Sistemática

Abstract: RESUMEN:Trasfondo: Durante los últimos años el entrenamiento interválico de alta intensidad (HIIT) ha aparecido como una alternativa saludable a nivel cardiaco, muscular y adiposo en diferentes colectivos. Pese a ser un tema frecuentemente tratado en la actualidad, no existe a día de hoy un consenso claro sobre su utilidad y aplicación en el colectivo de los adultos mayores. Objetivos: Examinar la literatura científica acerca del entrenamiento interválico de alta intensidad como medio de entrenamiento en perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The type of training to prevent OSO has also been studied, whether using the combination of aerobic exercises, and strength exercises, high-intensity aerobic exercises, and aerobics with changes in pace (HIIT and Fartlek). The latter two have shown better results since they combine rhythm changes promoting a continuous state of stress, which impacts on heart rate that is maintained several minutes after slowing down [ 13 , 15 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The type of training to prevent OSO has also been studied, whether using the combination of aerobic exercises, and strength exercises, high-intensity aerobic exercises, and aerobics with changes in pace (HIIT and Fartlek). The latter two have shown better results since they combine rhythm changes promoting a continuous state of stress, which impacts on heart rate that is maintained several minutes after slowing down [ 13 , 15 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Li and coworkers (2019) reported that tBHQ directly activates AMPK, although the exact mechanism is still unclear, while exercise is also known to increase AMPK activity by promoting molecular catabolism of glucose and fatty acids [ 13 ]. All the treatments are directly involved with lipid catabolism by activating beta oxidation-enzymes, as is the case of tBHQ that has been implicated in ACOX1 activation [ 6 , 13 , 37 ]. Moreover, exercise is the most studied mechanism related to lipid degradation since exercise promotes lipid catabolism due to the activation of various enzymes such as mLPL, a lipase known to increase its activity by 80% when people undergo moderate exercise regimen [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, aquatic exercise can ameliorate the negative physiological effects of aging, which are modifiable risk factors and predisposing factors for fall ( 26 ). On the other hand, interval training has been related as an alternative method for health improvement ( 27 ), so it could be related to increased performance and improvement of blood pressure, lipid profile, improved metabolic condition and strength gain ( 28 , 29 ). Also, it should be noted that there is an indirect relationship between fitness factors and some components of body composition, such as fat mass ( 30 ).…”
Section: Introductionmentioning
confidence: 99%